Design of a simulation tool for planning UAV mission success under combat constraints - Tyshchenko, Anton; Stopochkina, Iryna (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates unmanned aerial vehicle (UAV) networks operating under the influence of destructive and hostile factors. The study considers, among destructive factors, changes in signal power at the receiver side caused by distance and battery charge limitations. Among the hostile factors, cyber-physical threats have been examined, including those caused by electronic countermeasure (ECM) systems and malware-based attacks. Algorithmic and software solutions have been developed to simulate the behavior of UAVs under such constraints. A special feature of the proposed model, in contrast to existing approaches, is that it integrates factors such as signal degradation caused by ECM systems and the dynamics of malware propagation within the network. Scenarios include UAV behavior under jamming, the probabilistic spread of malware, and the switching of operational modes in response to threat exposure. The results were achieved by integrating a wide range of parameters, including device identifier, signal power, transmitter radius, transmission frequency, geolocation, task type, malware sensitivity, message handling queue, propagation delay, as well as movement speed. These features enable the model to realistically reproduce system behavior in uncertain and hostile environments, allowing both defensive and offensive security strategies to be explored. Devising appropriate operational scenarios is also possible. The proposed software solution is characterized by the high level of detail in the simulation and the use of the Rust programming language, which ensures performance, modularity, and future extensibility. The solution reported here supports visualization of the behavior of up to 100 UAVs and more through both images and animations. It can be used for analyzing attack scenarios, designing robust UAV architectures, and prototyping offensive security tools. The source code is publicly available at GitHub repository, supporting practical usage and further research applications